Factors Limiting Use of Poultry Manure as Protein Supplement for Dairy Cattle on Smallholder Farms in Kenya - Lanyasunya, T.P.; Rong, Wang H.; Abdulrazak, A.S.; Kaburu, P.K.; Makori, J.O.; Onyango, T.A.; Mwangi, D.M. (International Journal of Poultry Science, 2005)
Productivity of ruminant animals during the dry season, on smallholder farms in Kenya, is constraint by low availability and poor quality of the feeds (crop residues). The current study was conducted on smallholder farms in Nakuru, Koibatek and Trans Nzoia Districts in 2003 over 2-year period preceded by a 6 - week feed survey. The objective of the feed survey was to inventorize feed resources available on smallholder resource - poor farms and delineate factors limiting their optimization for enhanced dairy production. Other farm bio-data including livestock population (ruminants and poultry) and structure per farm were also collected. This paper confines its discussion on both qualitative and quantitative information gathered during the survey with special focus on poultry manure vis a vis litter and compares the results with reports other research works. During the survey, composite samples of feed resources being utilized at farm level (including poultry manure) were collected for dry matter (DM) determination and proximate analysis at the National Animal Husbandry Research Centre (NAHRC/Naivasha/Kenya. Results obtained, strongly indicated that, poultry manure has great potential for use during the dry season as a source of rumen degradable protein or non-protein nitrogen (NPN) in ruminant nutrition. Though heterogeneity was observed in the many reports reviewed and compared with the current study, the general consensus was that poultry manure/litter contains high level of crude protein (15 to 38%), fiber (11 - 52%), and rich in minerals (Ca: 0.81 - 6.13%; P: 0.56 - 3.92; K: 0.73 - 5.17), dry matter (61 - 95%). It is because of these nutrients that poultry manure has been deliberately mixed into ruminant livestock diets. Its Organic matter digestibility (OMD) ranges from 60 to 65, crude protein (CP) - 69.9, crude fibre (CF) - 29.9 and nitrogen-free extract (NFE) - 71.4%. Past research studies recorded in vitro dry matter digestibility (IVDMD) and IVOMD of 76.1 and 72.7%, respectively. Other reports also showed that, beef cattle fed poultry manure based diets recorded body weight gains ranging from 0.91 to 1.31 kg/d. Dairy goats supplemented with poultry manure registered 10.15% higher milk production compared to those on barley based diets (621 and 558 kg, respectively). Based on the available research information, it is conclude in this study that poultry manure can be successfully included in ruminant diets. The constraint, as revealed in the current study is that smallholder farmers do not own large chicken flock sizes (majority own less 30 birds) to guarantee sufficient supply of manure for ruminant feeding. It is this particular factor that is being attributed to the low poultry manure reported in the current study (regular users - 19%; occasional users - 17% and none users - 64%). Where available, poultry manure is very cheap. Since it is cheaply available (not readily) at farm level, poultry manure offers a cost effective option for meeting dairy cattle protein requirements. However, some precaution must be taken to minimize nitrogen loss (which occurs in the form of NH3, N2O and N2) and accumulation of pathogens (Salmonella and E. coli).